Long Term Assessment of a Research Curriculum for Obstetrics and Gynecology Residents. (October 2015) - Wagner, Sarah A.; Graziano, Scott; Mueller, Elizabeth; White, Paula; Fitzgerald, Colleen; Brubaker, Linda
Abstract : OBJECTIVE: To evaluate the effect of a structured research curriculum (Clinical Research Education Study Teams [CREST]) on scholarly productivity for residents in obstetrics and gynecology. METHODS: Program records were reviewed and each graduate's scholarly activity for the graduating classes of 2008–2015 was extracted. A control group consisted of the residents who had graduated in the decade before curriculum implementation. Graduates of the curriculum were surveyed to determine resident perception of their abilities pertaining to research after graduation. Continued engagement in research was also evaluated. Analytic tools were descriptive. RESULTS: The scholarly activity during residency was evaluated for the 31 residents who participated in the curriculum. Fifty-one scholarly products were identified (14 journal publications, 12 oral presentations, and 25 poster presentations). The average number of scholarly products was 6.38 per class and 1.34 per resident. Seven publications from 40 residents in the historic control group were identified (0.18 per resident). Seventy-eight percent of graduates responded to the survey. Graduates reported no concern for completion of the residency research requirement, felt better equipped to evaluate the literature, and felt more confident in their abilities to complete a research project. They reported continued productivity after graduation (mean 2.22 manuscripts). CONCLUSION: Obstetrics and gynecology residents who engaged in a structured clinical research curriculum (CREST) were significantly more active in clinical research than historic controls and presented their work frequently on the local, regional, and national level. Graduates of the program identified that this carried a sustained effect into their early careers.